Стрес змінює активність No-ергічної системи у м’язовій оболонці товстій кишці - Ємельяненко, В.Ю.; Панасюк, Н.Б.; Скляров, О.Я. (Таврический медико-биологический вестник, 2013)
В работе показано, что разные виды стресса (водно-имобилизационный, адреналин- индуцированный), а также экспериментальный колит вызывают увеличение активности индуцибельной NO-синтазы (iNOS) и процессов липопероксидации в мышечной оболочке толстой кишки, что может приводить к нарушению ее моторно-эвакуаторной функции. Stress is one of the factors, causing inflammation in the colon, promotes the development of ulcerative colitis in experimental animals and humans and worsens its course. The change of the motor-evacuating function of the digestive organs is one of the manifestations of the impact of stress. The mechanism of effect of stress is associated with the emergence of hypoxia due to vasoconstriction, changes in the activity of central and enteral neurons, increase of the lipid peroxidation processes, activation of NO-synthase and production of nitrogen oxide, that cause dysmotility of the colon.